2021
DOI: 10.3389/fpsyg.2021.671493
|View full text |Cite
|
Sign up to set email alerts
|

Higher Levels of Psychological Burden and Alterations in Personality Functioning in Crohn’s Disease and Ulcerative Colitis

Abstract: Aims: Is there evidence for increased psychological distress and alterations in personality functioning in patients with Crohn’s disease (CD) and ulcerative colitis (UC) compared to healthy controls (HCs)?Background: In patients with CD and UC, perceived stress is closely associated with changes in disease activity. The stress response is influenced by psychological burden and personality functioning, but only little is known about these factors in inflammatory bowel diseases (IBD).Study: A total of 62 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Previous neuroimaging studies have shown that the FPN is critical for the regulation of emotions. Our rs-FC findings in the FPN could be implicated in the inhibition of mentalization processes recently highlighted in patients with IBD ( Agostini et al, 2019 ; Engel et al, 2021 ). Chronic exposure to physical discomfort in the context of CD has been suggested to lead to reduced mentalization (the ability to understand one’s own behavior and the behavior of others) and result in alterations in brain areas that are involved in emotion processing.…”
Section: Discussionsupporting
confidence: 58%
“…Previous neuroimaging studies have shown that the FPN is critical for the regulation of emotions. Our rs-FC findings in the FPN could be implicated in the inhibition of mentalization processes recently highlighted in patients with IBD ( Agostini et al, 2019 ; Engel et al, 2021 ). Chronic exposure to physical discomfort in the context of CD has been suggested to lead to reduced mentalization (the ability to understand one’s own behavior and the behavior of others) and result in alterations in brain areas that are involved in emotion processing.…”
Section: Discussionsupporting
confidence: 58%
“…Among the included studies, three compared patients suffering from IBS with patients diagnosed with IBD [26][27][28], while other studies focused on patients with one of these conditions (IBS or IBD) and compared them with a control group [29][30][31][32]. RFS mean (SD) scores were 2.7 (1.4) for IBS, 1.4 (1.9) for NAP, and 3.3 (1.7) for AD.…”
Section: Resultsmentioning
confidence: 99%
“…There were differences between IBS-M and IBS-C (p = 0.023). No significant differences between IBS-M and IBS-D, and between IBS-D and IBS-C. With regard to the instruments used to assess mentalization, three studies used the Mentalization Questionnaire (MZQ) [26,28,31], two studies used the Metacognitions Questionnaire-30 (MCQ-30) [27,32], one study used both the Reflective Functioning Questionnaire (RFQ) and Reading the Mind in the Eyes Test (RMET) [29], and one study used both the Brief Reflective Function Interview (BRFI) and Reflective Functioning Scale (RFS) [30].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, psoriasis (PsO) is associated with psychological comorbidities, such as depression ( 3 ). Inflammatory bowel disease (IBD) patients have a higher level of depression and anxiety than healthy controls ( 4 ). Furthermore, autoimmune diseases can cause physical limitations or disabilities in patients with refractory to conventional treatments.…”
Section: Introductionmentioning
confidence: 99%